Comparative in vitro analysis of inhibition of rhinovirus and influenza virus replication by mucoactive secretolytic agents and plant extracts - Christin Walther; Kristin Döring; Michaela Schmidtke (BMC, 2020)
Abstract Background Rhinoviruses and influenza viruses cause millions of acute respiratory infections annually. Symptoms of mild acute respiratory infections are commonly treated with over-the-counter products like ambroxol, bromhexine, and N-acetyl cysteine, as well as of thyme and pelargonium extracts today. Because the direct antiviral activity of these over-the-counter products has not been studied in a systematic way, the current study aimed to compare their inhibitory effect against rhinovirus and influenza virus replication in an in vitro setting. Methods The cytotoxicity of ambroxol, bromhexine, and N-acetyl cysteine, as well as of thyme and pelargonium extracts was analyzed in Madin Darby canine kidney (MDCK) and HeLa Ohio cells. The antiviral effect of these over-the-counter products was compared by analyzing the dose-dependent inhibition (i) of rhinovirus A2- and B14-induced cytopathic effect in HeLa Ohio cells and (ii) of influenza virus A/Hong Kong/68 (subtype H3N2)- and A/Jena/8178/09 (subtype H1N1, pandemic)-induced cytopathic effect in MDCK cells at non-cytotoxic concentrations. To get insights into the mechanism of action of pelargonium extract against influenza virus, we performed time-of-addition assays as well as hemagglutination and neuraminidase inhibition assays. Results N-acetyl cysteine, thyme and pelargonium extract showed no or only marginal cytotoxicity in MDCK and HeLa Ohio cells in the tested concentration range. The 50% cytotoxic concentration of ambroxol and bromhexine was 51.85 and 61.24 μM, respectively. No anti-rhinoviral activity was detected at non-cytotoxic concentrations in this in vitro study setting. Ambroxol, bromhexine, and N-acetyl cysteine inhibited the influenza virus-induced cytopathic effect in MDCK cells no or less than 50%. In contrast, a dose-dependent anti-influenza virus activity of thyme and pelargonium extracts was demonstrated. The time-of addition assays revealed an inhibition of early and late steps of influenza virus replication by pelargonium extract whereas zanamivir acted on late steps only. The proven block of viral neuraminidase activity might explain the inhibition of influenza virus replication when added after viral adsorption. Conclusion The study results indicate a distinct inhibition of influenza A virus replication by thyme and pelargonium extract which might contribute to the beneficial effects of these plant extracts on acute respiratory infections symptoms.